2017
DOI: 10.1097/tp.0000000000001789
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of B Cell Recovery In Kidney/Bone Marrow Transplant Recipients

Abstract: Background Previous studies identified B cell gene signatures and predominance of specific B cell subsets as a marker of operational tolerance following kidney transplantation. These findings suggested a role for B cells in the establishment or maintenance of tolerance. Here we analyzed B cell recovery in 4 subjects, 3 of whom achieved tolerance after combined kidney/bone marrow transplantation. Methods Peripheral B cell subsets were examined longitudinally by flow cytometry. Immunoglobulin heavy chain reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…Reconstitution of the B cell pool after anti‐CD20 therapy occurs over a variable period of time depending on the species: for instance, murine B cell reconstitution can start as early as 4 weeks, although human B cell recovery begins over a span of 6‐12 months . Despite these kinetic differences, an interesting phenomenon described in both animals and humans is a preponderance of circulating TrBs during the reconstitution phase after anti‐CD20 therapy . In agreement with findings from other studies, we observed that rituximab induced a predominance of TrBs in the circulation of treated subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Reconstitution of the B cell pool after anti‐CD20 therapy occurs over a variable period of time depending on the species: for instance, murine B cell reconstitution can start as early as 4 weeks, although human B cell recovery begins over a span of 6‐12 months . Despite these kinetic differences, an interesting phenomenon described in both animals and humans is a preponderance of circulating TrBs during the reconstitution phase after anti‐CD20 therapy . In agreement with findings from other studies, we observed that rituximab induced a predominance of TrBs in the circulation of treated subjects.…”
Section: Discussionsupporting
confidence: 90%
“…B cell receptor repertoire reconstruction after CKBMT in four patients showed that the diversity of B‐cell receptors in graft‐tolerant subjects recovered to pre‐transplant levels after 1 year post‐transplantation.…”
Section: Immune Repertoire Profiling In Organ and Stem Cells Transplamentioning
confidence: 99%
“…In other conditions of hematopoietic cell recovery such as kidney or bone marrow transplantation, low B-cell counts are associated with slow B-cell reconstitution ( 62 , 63 ). In contrast, in our cohort, low B-cell counts pre-ART were rapidly normalized post-ART, suggesting a different mechanism of B-cell reconstitution than that reported for transplant recipients.…”
Section: Discussionmentioning
confidence: 99%